Psychometric analysis of a scale of conspirative beliefs in Peruvian population - López De Pomar, Fabrizio (2022)
Conspiratorial thinking is the tendency to attribute the causes of significant problems to secret plots schemed by people seeking to harm society. Although this trend has important consequences, there are no validated instruments that allow it to be measured in Spanish. The present study seeks to close this gap by translating and adapting the General Conspiracist Beliefs Scale (GCBS) into Spanish and analyzing its validity and reliability. For this, 316 participants were recruited from social networks to analyze the psychometric adequacy of the test. The validity evidence for the factorial structure of the test was confirmed with a structure of three factors: political, scientific, and alien conspiracies. Evidence of validity from the content of the test was adequate according to Aiken’s V coefficient. People with higher levels of conspiratorial thinking also had consistent responses on a conspiratorial thinking scale of one item; they trusted less in the effectiveness of scientific practices (and more in pseudoscientific practices) and exhibited lower levels of cognitive reflection, evidencing validity from the relationships with other variables. In conclusion, the GCBS is an adequate measure of conspiratorial thinking in Spanish.